Young children's use of their setting's internal floor space affordances: evidence from an ethnographic case study. Issue 10 (26th July 2020) - Katsiada, Eleni; Roufidou, Irini
ABSTRACT: Young children's use of their Early Childhood Education and Care (ECEC) environment affordances, and especially the affordances of the floor, is an under researched area, both in Greece and internationally. This paper draws on findings from an ethnographic case study research conducted in Greece and presents an account of children's multidimensional use of their settings and particularly the floor space within the settings. Ten children, under the age of three, participated in the study. Data was collected using an adaptation of the Mosaic Approach (Clark & Moss, 2001, Listening to young children: The mosaic approach . London: Jessica Kingsley) and analyzed using data-driven thematic analysis (Boyatzis, 1998, Transforming qualitative information: Thematic analysis and code development . London: Sage). The findings suggest that the case study children value, more than adults, the floor's affordances and the vast opportunities it offers for play, exploration and socialization, whilst it also assists them to express agency.